Two-Phase Two-Stage HF Matrix Converter for Supplying Two-Phase Motor Load - Prazenica, Michal; Kabasta, Michal; Kascak, Slavomir; Koscelnik, Juraj; Buday, Jozef (Communications - Scientific letters of the University of Zilina, 2013)
This paper deals with the two-stage two-phase electronic systems with orthogonal output voltages and currents – DC/HF_AC/2AC. It also introduces the design and prototype of two-stage DC/HF_AC/2AC high frequency converter with two-phase orthogonal output using two singlephase matrix converters in full-bridge connection operated with the unipolar PWM. Simulation and experimental results of matrix converter for both steady and transient states for IM motors are given in the paper together with experimental verification under R-L load. The results confirm a very good time-waveform of the phase current and the system seems to be suitable for low-cost application in automotive/aerospace industries and application with high frequency voltage sources.